MANAJERIAL ENTRENCHMENT DAN EARNINGS MANAGEMENT - Yovinianus Usboko; Permata Ayu Widyasari (Perpustakaan Universitas Surabaya, 2021)
Abstract — The preparation of financial statements requires management expertise and reliability to be easily understood and easily used by stakeholders of financial statements. Financial statements are a tool to find out how the actual condition of a company. The preparation of financial statements requires management expertise and reliability to be easily understood and easily used by stakeholders of financial statements. But in reality, there have been many manipulations of financial statements. This manipulation can occur because management is forced to always fulfill the wishes of shareholders. This study examines how the CEO's working relationship, the percentage of share ownership with earnings management carried out by management. The data used is the financial statements of companies engaged in manufacturing that are listed on the Stock Exchange. This study found that the higher the CEO work relationship, the higher the earnings management carried out while the number of CEO shares ownership was not related to earnings management. Keywords: CEO tenure, earnings management, managerial ownership Abstrak — Penyusunan laporan keuangan memerlukan keahlian dan keandalan manajemen agar mudah dipahami dan mudah digunakan oleh pemangku kepentingan dari laporan keuangan. Laporan keuangan merupakan suatu alat bantu untuk mengetahui bagaimana keadaan suatu perusahaan yang sebenarnya. Penyusunan laporan keuangan memerlukan keahlian dan keandalan manajemen agar mudah dipahami dan mudah digunakan oleh pemangku kepentingan dari laporan keuangan. Tetapi pada kenyataanya, banyak terjadi manipulasi pada laporan keuangan. Manipulasi ini bisa terjadi karena pihak manajemen yang dipaksa selalu untuk memenuhi keinginan pemegang saham. Penelitian ini meneliti bagaimana hubungan kerja CEO, persentase kepemilikan saham dengan manajemen laba yang dilakukan oleh pihak manajemen. Data yang digunakan adalah laporan keuangan perusahaan yang bergerak pada bidang manufaktur yang tedaftar di BEI Penelitian ini mendapatkan hasil semakin tinggi hubungan kerja CEO akan semakin tinggi manajemen laba yang dilakukan sedangkan jumlah kepemilikan saham CEO tidak berhubungan dengan manajemen laba. Kata kunci: hubungan CEO, kepemilikan manajer, manajemen laba